What do Canadian agricultural policies support? - Talan İşcan; Kathleen Kevany; Anthony Weis (Canadian Food Studies / La Revue canadienne des études sur l'alimentation, 2026)
Industrial agri-food systems and food consumption patterns in high-income countries contribute to a range of environmental problems, including greenhouse gas emissions, biodiversity loss, persistent toxicity, and freshwater pollution. Industrial agri-food systems also receive considerable government support in many high-income countries. This study provides a critical assessment of Canadian agricultural production support policies, showing how they have overwhelmingly focussed on increasing the volumes and export competitiveness of a small range of feed crops, food grains, and livestock production, ultimately subsidizing energy- and input-intensive practices. Our analysis also reveals how these support policies have mostly served to enhance the revenues and incomes of relatively higher-income farmers, during a period marked by the dramatic consolidation of farms and the concentration along the agricultural supply chain, while doing little to stabilize the livelihoods of small- and medium-scale farmers, evident in the steep decline in the number of smaller farms. Our central aim is to explain how Canada’s agricultural production support policies make key aspects of its agri-food system worse not better, and why there is an urgent need to reorient these policies to focus on improved environmental sustainability, distributional outcomes, and public health.